Comparative industrial relations : an introduction to cross-national perspectives - Bean, R. (Ron), 1938- (London : International Thomson Business Press, 1996)
Introduction. Trade unions. Employers and managements. Collective bargaining. The role of state. Industrial conflict and strikes. Workers' participation in decision-making...
Keywords: Economics; Industry; Industrial relations; Comparative industrial relations; Industrial relations -- Cross-cultural studies